2010
DOI: 10.1038/npp.2010.36
|View full text |Cite|
|
Sign up to set email alerts
|

Nitric Oxide Synthase Mediates the Ability of Darbepoetin Alfa to Improve the Cognitive Performance of STOP Null Mice

Abstract: STOP (stable tubule only polypeptide) null mice display neurochemical and behavioral abnormalities that resemble several well-recognized features of schizophrenia. Recent evidence suggests that the hematopoietic growth factor erythropoietin improves the cognitive performance of schizophrenics. The mechanism, however, by which erythropoietin is able to improve the cognition of schizophrenics is unclear. To address this question, we first determined whether acute administration of the erythropoietin analog known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
(82 reference statements)
1
13
0
1
Order By: Relevance
“…Ayrıca, şizofreninin değişik yönlerini hedef alan hayvan modellerinde NO sinyal iletiminin değiştiği ortaya konmuştur (Ribeiro ve ark. 2013, Kajitani ve ark. 2010.…”
Section: Introductionunclassified
“…Ayrıca, şizofreninin değişik yönlerini hedef alan hayvan modellerinde NO sinyal iletiminin değiştiği ortaya konmuştur (Ribeiro ve ark. 2013, Kajitani ve ark. 2010.…”
Section: Introductionunclassified
“…Recently, Kajitani et al (2010) reported observations to support that enhanced nitric oxide signaling might be the mechanistic basis for erythropoietin's cognitive benefits in schizophrenia. However, numerous studies have suggested that enhanced nitric oxide signaling might adversely impact schizophrenia.…”
mentioning
confidence: 95%
“…However, numerous studies have suggested that enhanced nitric oxide signaling might adversely impact schizophrenia. For example, increased nitric oxide signaling has been demonstrated to underlie the information-processing deficits in the phencyclidine model of schizophrenia (Palsson et al, 2010); intriguingly, the nitric oxide synthase inhibitor (N (G)-nitro-L-arginine methyl ester (L-NAME)) used by the authors in this study (Kajitani et al, 2010) has been reported to ameliorate the phencyclidine-induced cognitive deficits (Klamer et al, 2001). Moreover, treatment with minocycline, a nitric oxide synthase inhibitor, improved cognitive deficits in schizophrenia patients in a double-blind, randomized, placebo-controlled study (Levkovitz et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies showed that MAP6 knockout mice have reduced number of synaptic vesicles and impaired synaptic plasticity (Andrieux et al 2002). Later, it was shown that, in addition to changes in glutamatergic synaptic transmission, these mice also present alterations in dopaminergic, acetylcholinergic, nicotinic, serotonergic, and noradrenergic neurotransmission (Bouvrais-Veret et al 2007, 2008Brun et al 2005;Delotterie et al 2010;Fournet et al 2010Fournet et al , 2012bFradley et al 2005;Kajitani et al 2010;Powell et al 2007). These alterations recapitulate some clinical features observed in schizophrenia disorders (Andrieux et al 2002;Fournet et al 2012b).…”
Section: Map6 Family Of Microtubule-associated Proteinsmentioning
confidence: 99%